2013
DOI: 10.1364/oe.21.020880
|View full text |Cite
|
Sign up to set email alerts
|

Compact polarizing beam splitter based on a metal-insulator-metal inserted into multimode interference coupler

Abstract: We propose and analyze a compact polarizing beam splitter (PBS) based on a metal-insulator-metal (MIM) structure inserted into a multimode interference coupler (MMI). Owing to the MIM structure, the TE polarized state is reflected by the cut-off condition while the TM polarized state is transmitted by the surface plasmon polariton, and the two polarized states can thus be separated. In this paper, the dependence of the reflected TE and transmitted TM field intensities on the MIM length and the gap thickness ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For broadband polarization splitting, multimode interference couplers (MMIs) are particularly promising candidates. PBSs based on conventional MMIs have comparatively large footprints [19], [20], which can be reduced by using quasi-imaging [21], photonic crystals [22], slot waveguides [23], metalinsulator-metal structures [24] and augmented-low-index-guiding waveguides [25]. In particular, the inherent anisotropy of SWG enables MMIs with virtually wavelength independent beat lengths for TE polarization, thereby enabling ultra-broad bandwidths.…”
Section: Introductionmentioning
confidence: 99%
“…For broadband polarization splitting, multimode interference couplers (MMIs) are particularly promising candidates. PBSs based on conventional MMIs have comparatively large footprints [19], [20], which can be reduced by using quasi-imaging [21], photonic crystals [22], slot waveguides [23], metalinsulator-metal structures [24] and augmented-low-index-guiding waveguides [25]. In particular, the inherent anisotropy of SWG enables MMIs with virtually wavelength independent beat lengths for TE polarization, thereby enabling ultra-broad bandwidths.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, polarization diversity scheme is often used, 2 where polarization beam splitter (PBS), efficiently separating the TE and TM modes, is a fundamental component. So far, there have been many kinds of approaches reported for designing and/or fabricating a compact PBS with various structures, e.g., directional couplers (DCs), 3,4 multimode interference (MMI) couplers, 5,6 Mach-Zehnder interferometers, 7 photonic crystal structures. 8 Moreover, hybrid plasmonic waveguide (HPW), which confines mode within the low index gap between a metal cap and a high index dielectric layer, and long-range surface plasmon polariton (LR-SPP) waveguide, have also been introduced into the design of PBS.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many types of PBSs 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 have been reported that have utilized various designs and have included adiabatic mode evolution (AME) devices 6 7 , directional couplers (DC) 8 9 10 11 12 13 14 15 16 17 18 19 20 , multimode interference (MMI) devices 21 22 23 24 25 , Mach–Zehnder interferometers (MZI) 26 27 28 , photonic crystals (PhC) 29 30 31 , and grating 31 32 33 structures. Most PBSs 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 28 32 33 …”
mentioning
confidence: 99%
“…Although the device lengths of DC-based PBSs 8 9 10 11 12 13 14 15 16 17 18 19 20 can be reduced to several to tens of micrometers with reasonable PERs (10–20 dB), operating bandwidths are narrower than those of AME-based PBSs because of the requirement of utilizing phase-matched modes with a precisely tuned coupling. MMI-based PBSs 21 22 23 24 25 have a simpler fabrication process and larger fabrication tolerance than those of AME-based PBSs; however, dimensions of conventional MMI devices 35 36 are determined by the common multiple of the self-imaging lengths 37 of TE and TM modes, resulting in very long devices (>1000 μm). To shorten the lengths of MMI-based PBSs, some innovative designs have recently been reported, including two-mode interference 21 (~8.8 μm), 2 × 2 two-mode interference 22 (~0.94 μm for the length of MMI section only other than the whole PBS, the lengths for the input/output part should be included), metal–insulator–metal (MIM)-embedded 22 (~44 μm), hybrid plasmonic waveguide (HPW) 24 (~2.5 μm), and cascaded 25 (<950 μm) MMIs.…”
mentioning
confidence: 99%
See 1 more Smart Citation